2002
DOI: 10.1177/1087057102238630
|View full text |Cite
|
Sign up to set email alerts
|

A Standard Operating Procedure for Assessing Liquid Handler Performance in High-Throughput Screening

Abstract: The thrust of early drug discovery in recent years has been toward the configuration of homogeneous miniaturized assays. This has allowed organizations to contain costs in the face of exponential increases in the number of screening assays that need to be run to remain competitive. Miniaturization brings with it an increasing dependence on instrumentation, which over the past several years has seen the development of nanodispensing capability and sophisticated detection strategies. To maintain confidence in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 32 publications
0
57
0
Order By: Relevance
“…It is the second challenge for which inkjet printing was identified as a potentially important tool (Blanchard et al 1996, Lemmo et al 1997, Sittampalam et al 1997, Burbaum et al 1997, Lemmo et al 1998, Oldenburg et al 1998, Schena et al 1998, Rose 1999, Dunn and Feygin 2000, Bellavance et al 2000, Taylor et al 2002. The key features of inkjet that lend themselves to the liquid handling challenges of micro-array technologies are (i) noncontact deposition with a significant stand-off distance, ensuring that the size of the well is no longer limited by the size of the dosing nozzle, (ii) repeatability and accuracy of inkjet-deposited drops once their formation is optimised, (iii) accurate control of both individual drop volumes and total volumes by waveform and print signal controls, (iv) low reservoir volume requirements and (v) minimal space requirements for the system.…”
Section: High Throughput 'System Discovery' Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the second challenge for which inkjet printing was identified as a potentially important tool (Blanchard et al 1996, Lemmo et al 1997, Sittampalam et al 1997, Burbaum et al 1997, Lemmo et al 1998, Oldenburg et al 1998, Schena et al 1998, Rose 1999, Dunn and Feygin 2000, Bellavance et al 2000, Taylor et al 2002. The key features of inkjet that lend themselves to the liquid handling challenges of micro-array technologies are (i) noncontact deposition with a significant stand-off distance, ensuring that the size of the well is no longer limited by the size of the dosing nozzle, (ii) repeatability and accuracy of inkjet-deposited drops once their formation is optimised, (iii) accurate control of both individual drop volumes and total volumes by waveform and print signal controls, (iv) low reservoir volume requirements and (v) minimal space requirements for the system.…”
Section: High Throughput 'System Discovery' Techniquesmentioning
confidence: 99%
“…Potyrailo et al 2007 discussed the existence of applications outside pharmaceuticals for this technology, in a similar way to combinatorial chemistry. Earlier work by GlaxoSmithKline Pharmaceuticals (Taylor et al 2002) showed that piezo-actuated inkjet and capillary deposition were the only non-contact techniques that could be tailored to the correct throughput and reliability for this approach. (Boehm et al 2011).…”
Section: High Throughput 'System Discovery' Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of instrument performance has become important in order to minimize falsepositive and false-negative rates in high-throughput screening (Taylor et al 2002). One of the most important figures of merit in evaluating the performance of liquid handlers is accuracy, which is commonly reported as %bias (Rose 1999):…”
Section: Determination Of Quality Assessment Descriptorsmentioning
confidence: 99%
“…Gravimetric measurements utilize the mass and the density (ρ) of the dispensed solution to determine the volume. It has been used extensively to calibrate and verify the accuracy of liquid dispensers (Bergsdorf et al 2006;Rhode et al 2004;Taylor et al 2002). Typically, the solution is dispensed across a pre-weighed microtiter plate, which is weighed immediately after dispensing to prevent evaporation.…”
Section: Determination Of Quality Assessment Descriptorsmentioning
confidence: 99%